Does Personality and Anxiety Symptomatology Matter in the Diabetes Mellitus Treatment Adherence? A Cross-Sectional Study Among Women with Diabetes Mellitus. - Woon, Luke; Autar Singh, Gurpreet Kaur; Sidi, Hatta (IIUM Medical Journal Malaysia, 2021)
Abstract Purpose: Anxiety is prevalent among women with diabetes mellitus. Women also tend to have higher levels of neuroticism and anxiety. These symptoms can have an impact on social functioning and diabetes care. The main aim of the present study was to determine the relationship between neuroticism and anxiety symptoms, and other clinical and psychosocial variables, among women with diabetes mellitus (DM). Patients and methods: This was a cross-sectional study conducted on women with diabetes mellitus. Sociodemographic and clinical variables were acquired, including perceptions on religious practice, social support, and diabetic self-care. Study subjects completed the Generalized Anxiety Disorder 7-item (GAD-7) and the Big-Five Inventory (BFI). The neuroticism subscale of the BFI was used for analysis. Results: The study included 141 subjects (Median age: 64.0 years, IQR: 52.5–71.0 years) with a median duration of diabetes of 12.0 years (IQR: 6.0–20.0 years). Neuroticism scores correlated positively with the GAD-7 scores (Spearman’s rho: 0.406; p<0.001). In the bivariate analysis, neuroticism also had significant association with employment status (p=0.023), religious practice (p=0.006), perceived social support (p=0.001), and perceived ability of diabetic self-management (p<0.001). In the regression analysis, after controlling for employment, religious practice, and social support, neuroticism remained associated with anxiety (p<0.001) and diabetic self-management (p=0.001). Conclusions: Neuroticism was related to poorer subjective sense of diabetic management and a greater level of anxiety among women with DM. Improving self-efficacy in managing diabetes may help patients coping up with anxiety symptoms among those with neuroticism traits. This may also contribute to a better understanding of features and effective treatment of women with DM.